A study on the impact mechanism of internet embedding on rural E-commerce entrepreneurship - Song, Ying; Yang, Lu; Li, Lu (Research in international business and finance, 2024)
In the context of the rapid development of global Internet and e-commerce, rural e-commerce entrepreneurship has become an important driving force for rural e-commerce development. Using micro-survey data from five national e-commerce demonstration counties in China, this paper empirically examines the impact of Internet embedding on rural e-commerce entrepreneurship and the mediation effect of social capital. The results show that farmers are more likely to choose an independent entrepreneurship channel than a cooperative entrepreneurship channel when the Internet is embedded in rural areas. Then, social capital plays a suppressing effect between Internet embedding and farmers’ e-commerce entrepreneurial choices. In addition, under the condition of Internet embedding, farmers with more social capital are more likely to choose cooperative e-commerce entrepreneurship channels. [Display omitted] •This article contributed a new perspective and theoretical logic to farmers entrepreneurship research.•Study the impact of rural Internet applications on the choice of e-commerce entrepreneurial.•Social capital plays a suppressing effect between Internet embedding and farmers’ e-commerce entrepreneurial choices.•Both e-commerce organizational forms arise endogenously as an optimal response to incentives given farmers’ resources.